Strategi Pemasaran Pakan Ikan Di Sumatera Utara - Harahap, Abdul Anas; Kuswardani, Retna Astuti; Wahyono, Teguh (Universitas Medan Area, 2021)
This study aims to (1) determine the feed marketing channel system carried out by the company to consumers (2) to determine the development of feed marketing during the last five years obtained by the company PT. Suri Tani Perdana (3) To determine the factors that affect feed in the company PT. Suri Tani Perdana. The form of this research is descriptive quantitative research using secondary data. Namely time series data (time series) with the method of observation (survey) directly to the company PT. Suri Tani Perdana. The analysis used is analysis using verbalistic and graphic methods, time series trend analysis using the ordinary least square (OLS) method. The quantitative analysis used is by observing the secondary data of the company PT STP (Persero), using simple linear regression analysis. The reason is to see the relationship between feed prices and marketing of feed products.